2020
DOI: 10.1097/sr9.0000000000000009
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate antibiotics in dog bite injuries: an audit study

Abstract: Background: Dog bite injuries are a common presentation to Accident and Emergency. In the United Kingdom ~250,000 people attend emergency units each year as a result of dog wounds. Currently, there is a lack of consistency in the approach and management of such wounds across plastic surgery units in the United Kingdom. Method: A retrospective review of medical record of patients who were admitted under the care of the Plastic Surgery Department at Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
4
0
4
Order By: Relevance
“…This problem has also been documented in other countries; for example, in Australia, Birdsey et al (2016) reported that 38.1% of patients were not treated in accordance with the Australian Therapeutic Guidelines for animal bites; among these patients, 18.7% were prescribed a non‐recommended antibiotic, 11.9% had indications for antibiotics but did not receive a prescription, and 7.5% were prescribed an antibiotic without indications. Similarly, in Australia, Baxter et al (2020) reported that in 27.5% of cases, antibiotics were used without clinical criteria, and in the United Kingdom, Al Omran et al (2020) reported that 20.0% of patients received ineffective antibiotics, based on clinical practice guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…This problem has also been documented in other countries; for example, in Australia, Birdsey et al (2016) reported that 38.1% of patients were not treated in accordance with the Australian Therapeutic Guidelines for animal bites; among these patients, 18.7% were prescribed a non‐recommended antibiotic, 11.9% had indications for antibiotics but did not receive a prescription, and 7.5% were prescribed an antibiotic without indications. Similarly, in Australia, Baxter et al (2020) reported that in 27.5% of cases, antibiotics were used without clinical criteria, and in the United Kingdom, Al Omran et al (2020) reported that 20.0% of patients received ineffective antibiotics, based on clinical practice guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Amoxicillin/clavulanic acid is the first-choice agent both for prophylaxis and treatment for DBW patients who are not penicillin allergic [ 48 ]. The present study demonstrated that amoxicillin/clavulanic acid was resistant to only 14% of the isolates, which was lower in some earlier studies [ 31 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the observed differences in the levels of susceptibility between amoxicillin/clavulanic acid and oxacillin may require further investigation. Furthermore, beyond UCG, Metronidazole is recommended to treat infection in DBWs [ 18 , 44 ] especially for those allergic to penicillin [ 48 ]. In this study, all isolates were resistant to metronidazole which is known to be generally effective against Gram-negative anaerobes.…”
Section: Discussionmentioning
confidence: 99%
“…Es ist bei Bisswunden grundsätzlich davon auszugehen, dass eine polymikrobielle Kontamination des Wundgebietes vorliegt [ 22 , 23 ]. Die Breite des Erregerspektrums korreliert mit der Schwere der resultierenden Infektion: Bei Hundebissen sind die häufigsten Erreger (30–60 %) Pasteurella -Spezies, hämolysierende Streptokokken, Staphylococcus aureus sowie Mischinfektionen mit Anaerobiern [ 23 , 24 ]. Infektionserreger nach Katzenbissen sind in über 50 % der Fälle Pasteurella multocida meist mit aerob-anaerober Mischinfektion [ 23 ].…”
Section: Diagnostikunclassified